2016
DOI: 10.1007/s10344-016-1000-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated removal activities on movements and space use of feral swine

Abstract: Abundance and distribution of feral swine (Sus scrofa) in the USA have increased dramatically during the last 30 years. Effective measures are needed to control and eradicate feral swine populations without displacing animals over wider areas. Our objective was to investigate effects of repeated simulated removal activities on feral swine movements and space use. We analyzed location data from 21 feral swine that we fitted with Global Positioning System harnesses in southern MO, USA. Various removal activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
(38 reference statements)
2
11
0
Order By: Relevance
“…This could be related to these animals relying on anthropogenic food sources during periods of food stress 17,19 . However, this result also indicated that wild pigs did not become conditioned to avoid using the bait sites, which has been suggested in other studies 22,24 . This is good news for elimination programs that use bait visitation as a strategy to detect wild pigs.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This could be related to these animals relying on anthropogenic food sources during periods of food stress 17,19 . However, this result also indicated that wild pigs did not become conditioned to avoid using the bait sites, which has been suggested in other studies 22,24 . This is good news for elimination programs that use bait visitation as a strategy to detect wild pigs.…”
Section: Discussionsupporting
confidence: 71%
“…We also found that wild pigs used bait sites more during evening and nocturnal periods, which coincides with nocturnal behaviors, particularly for persecuted animals. Efforts to remove wild pigs have resulted in modification of behaviors to avoid detection by becoming more nocturnal 59 and increasing movement rates [22][23][24] . Snow et al 60 reported that wild pig visitation rates to bait sites for a hunted population in south-central Texas peaked between 1900-0200 h. However, shifts in behaviors have not been reported for all populations of wild pigs 61 and www.nature.com/scientificreports/ therefore it may depend on the intensity of persecution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a 2-year old sow with her piglets covered a distance of at least 500 km within two months 19 . Reports on daily distances travelled by wild boars differ considerably in the literature 20 22 and vary, for example, from 2.7 km to 6.8 km and partly more than 12 km depending on sex, age, season or available resources, but also affected by the animal habitat such as urban area or primeval forest.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in conditions could result in variation in the area of influence. The area of influence may vary due to a combination of biological limitations such as movement behavior (Baber and Coblentz, 1986;Saunders and McLeod, 1999;Fischer et al, 2016), or environmental factors such as resource availability (Saunders et al, 1993;Caley, 1994), weather (Wyckoff et al, 2006), and trap type or duration of trapping (Caley, 1994;Williams et al, 2011). Understanding effects of these factors on area of influence is not only relevant to obtaining better estimates of disease control impacts but also to planning efficient resource allocation for risk assessment and responding to disease outbreaks.…”
Section: Discussionmentioning
confidence: 99%